(3aJhM GdZjHs - (3YHO GdbGOQ Hf CHj UGdM Hf YHO Gddg GdLjdGfj, CHh eMeO,J (B561 (3g` s ((3eMeO Hf GdMSf GdHcQj s)
(3ChdgG (B:s
(3CeG HYO aEf fYe Gddg YdjfG cKjQI eJhGJQI oeJQGOaI eJTGHgI eJhGdjI eJQGSdI s
(3BNQgG (B:s
(3hJMbjb GdYhV haj GdCNQi Ydi ef PcQfG BNQ GdLRA GdChd ef cJGH GdaJhM s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1240s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY(B) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs